Toward an Integrated Physiological Theory of Microbial Growth: From Subcellular Variables to Population Dynamics - Atul Narang; Sergei S. Pilyugin (Mathematical Biosciences and Engineering)
The dynamics of microbial growth is a problem of fundamental interest in microbiology,microbial ecology, and biotechnology. The pioneering work of JacobMonod, served as a starting point for developing a wealth of mathematicalmodels that address different aspects of microbial growth inbatch and continuous cultures. A number of phenomenological modelshave appeared in the literature over the last half century. Thesemodels can capture the steady-state behavior of pure and mixed cultures,but fall short of explaining most of the complex dynamic phenomena.This is because the onset of these complex dynamics is invariablydriven by one or more intracellular variables not accountedfor by phenomenological models.  &nbsp In this paper, we provide an overview of the experimental data, andintroduce a different class of mathematical models that can be usedto understand microbial growth dynamics. In addition to the standardvariables such as the cell and substrate concentrations, these modelsexplicitly include the dynamics of the physiological variables responsiblefor adaptation of the cells to environmental variations. We presentthese physiological models in the order of increasing complexity.Thus, we begin with models of single-species growth in environmentscontaining a single growth-limiting substrate, then advance to modelsof single-species growth in mixed-substrate media, and conclude withmodels of multiple-species growth in mixed-substrate environments.Throughout the paper, we discuss both the analytical and simulationtechniques to illustrate how these models capture and explain variousexperimental phenomena. Finally, we also present open questions andpossible directions for future research that would integrate thesemodels into a global physiological theory of microbial growth.